Study the effect of nickel and aluminium doped ZnO photoanode in DSSC - Nur Syafiqah Nadiah Mohd Alias; Faiz Arith; Nur Syamimi Noorasid; Hafez Sarkawi; Ahmad Nizamuddin Muhammad Mustafa; Mohd Muzafar Ismail; Mohd Khanapiah Nor (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
Dye sensitized solar cells (DSSC) is one of the promising candidates which are efficient, low-cost, and clean hybrid molecular solar cell devices. Zinc oxide (ZnO) has been widely used as the phoanode in DSSC due to its excellent charge conduction mechanism, yet still suffers from poor cell efficiency. In this study, aluminium doped ZnO (ZnO:Al) and Ni doped ZnO (ZnO:Ni) were studied as photoanode material in DSSC using solar cell capacitance simulator (SCAPS) simulation, and the electrolyte liquid considered a single solid p-type layer as hole transporting materials. Both studied photoanodes have demonstrated better cell performance than pure ZnO photoanode due to the small amount of aluminium (Al) and nikel (Ni) impurities added have enhanced the physiochemical properties of ZnO films. A power conversion efficiency (PCE) of 3.96% was obtained at 3 mol% ZnO:Al photoanode with optimized key parameters. These simulation results proved an opportunity to improve the performance of the DSSCs via doping engineering into the ZnO photonaode.